The Role of Financial Technology (FinTech) in Corruption Prevention: An Analysis of Digital Transaction Transparency - Beesokhi Ndruru Beesokhi Ndruru; Hendri Jayadi; Richard M. Nainggolan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid development of Financial Technology (Fintech) has transformed the financial system by enabling faster, more efficient, and transparent digital transactions. At the same time, this development has created legal challenges related to regulatory certainty, personal data protection, and supervision of digital transactions that may facilitate corruption. This study aims to analyze the legal framework governing Financial Technology in supporting digital transaction transparency and to examine the role of fintech in strengthening digital transaction transparency as a preventive measure against corruption in Indonesia. This research employs a normative legal research method using statutory, conceptual, and analytical approaches. The legal materials consist of primary, secondary, and tertiary sources analyzed through qualitative legal analysis. The findings indicate that Indonesia has established a relatively comprehensive legal framework through Law Number 4 of 2023 on the Development and Strengthening of the Financial Sector, Law Number 1 of 2024 on Electronic Information and Transactions, Law Number 27 of 2022 on Personal Data Protection, as well as regulations issued by Bank Indonesia and the Financial Services Authority. Fintech implementation generates a digital audit trail that enhances transparency, accountability, and supervisory effectiveness in financial transactions. Based on the Theory of Legal Certainty, Legal System Theory, and Good Governance Theory, fintech serves as an important instrument in promoting transparent, accountable, and integrity-based financial governance, thereby strengthening corruption prevention efforts. Nevertheless, continuous regulatory harmonization, stronger inter-agency coordination, improved cybersecurity, and enhanced digital literacy remain essential to optimize fintech implementation.